Cross Hedging Cull Cows - Graff, Jennifer L.; Schroeder, Ted C.; Jones, Rodney D. (My University, 1997)
This publication for beef producers describes cross heading cull cows based on weekly data from several locations and across several cow grades.
MF2267_1997_04
Keywords: MF2267; Livestock; Economics; MF